Ways of Intensification of Grass Seed Production - Spirin A.; Borysiuk D.; Tsurkan O.; Tverdokhlib I.; Veselovska N.; Edl M. (Журнал інженерних наук)
The main reason that restrains the development of seed production of perennial grasses is losses during harvesting, which depend on the agrotechnical properties of plants and the imperfection of existing means. There are no special grass seeds yet. Therefore, serial equipment with special devices is recommended for their collection. There are enough options for technologies for collecting grass seeds. In the article, six main options of technologies used in production were analyzed and compared according to the main indicators. The best results of a comprehensive comparison are those technologies that process the collected seed mass into a stationary one. The design of a device for wiping the seed mass was proposed to develop this direction of grass seed collection technologies. The article presents theoretical and experimental research results that allowed improving these devices based on rational design and operating parameters. Another way to intensify the production process of leguminous grass seeds is to combine the technological processes of wiping and separation in one machine. The analysis of various separating devices showed that machines with a rotating screen of cylindrical or conical shape are best suited for this purpose. The conducted theoretical studies confirmed the hypothesis that extending the time the material stays on the sieve by using a conical surface increases the yield of clean seeds and contributes to uniform loading of the sieve surface, improving the quality of the initial material. According to the research results, the design of the grating-separating block was proposed for the implementation of this scientific hypothesis. The theoretical and experimental studies presented in the article will allow for significantly intensifying the process of collecting grass seeds and outlining the further development of scientific research in this field.